2018
DOI: 10.3389/fphar.2018.00396
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Therapeutic Strategies for Cystic Fibrosis: Moving Forward to CRISPR Technique

Abstract: One of the most revolutionary technologies in recent years in the field of molecular biology is CRISPR-Cas9. CRISPR technology is a promising tool for gene editing that provides researchers the opportunity to easily alter DNA sequences and modify gene function. Its many potential applications include correcting genetic defects, treating and preventing the spread of diseases. Cystic fibrosis (CF) is one of the most common lethal genetic diseases caused by mutations in the CF transmembrane conductance regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 34 publications
0
39
0
Order By: Relevance
“…Areas for future research include testing of the CFTR transcript and activity levels in different samples including nasal cells and organoids [39•] among patients with the CFTR I1234V mutation, as studies have shown that organoids may be used for the development of personalized treatment for patients with CF [40•, 41•]. Applying Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) technology as a tool for gene editing along with its promising results as shown elsewhere on other mutations [2] is yet to take place for the CFTR I1234V mutation. In conclusion, a better future for CF patients worldwide and locally in Qatar is contingent upon intensifying research efforts and expanding on current collaborations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas for future research include testing of the CFTR transcript and activity levels in different samples including nasal cells and organoids [39•] among patients with the CFTR I1234V mutation, as studies have shown that organoids may be used for the development of personalized treatment for patients with CF [40•, 41•]. Applying Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) technology as a tool for gene editing along with its promising results as shown elsewhere on other mutations [2] is yet to take place for the CFTR I1234V mutation. In conclusion, a better future for CF patients worldwide and locally in Qatar is contingent upon intensifying research efforts and expanding on current collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…The cause is a mutation in the gene that encodes the cystic fibrosis transmembrane conductance regulator (CFTR) protein [1]. The number of CFTR gene mutations exceeds 2000 so far [2]. CF involves the presence of two disease-causing mutations on two separate chromosomes [3].…”
Section: Introductionmentioning
confidence: 99%
“…While systemic delivery of pharmacological agents is successful for many conditions, the targeting of genetic therapies via systemic administration is only likely to be feasible if there are bone marrow precursors of the cellular target, or a method to preferentially deliver a systemically administered agent to lung tissues. In the case of CF, intravenous delivery would only reach the alveolar surface of the lung and not the surface epithelium of the bronchioles where CFTR is expressed …”
Section: Challenges In Applying Crispr/cas Gene Editing For Respiratomentioning
confidence: 99%
“…Direct delivery to the lung via aerosol or direct intratracheal instillation might be a feasible alternative to systemic administration. However, these approaches also have many challenges, particularly in the presence of significant heterogeneous disease expression, airway mucus, mucociliary clearance and immune responses . For example, structural lung abnormalities in CF patients are known to influence the deposition patterns of inhaled therapeutic agents, resulting in an impaired effect of treatment .…”
Section: Challenges In Applying Crispr/cas Gene Editing For Respiratomentioning
confidence: 99%
See 1 more Smart Citation